Towards a victimology of state crime - Rothe, Dawn, 1961-; Kauzlarich, David (Milton Park, Abingdon, Oxon, UK : Routledge, 2014)
Millions of people have been victimized by the actions and omissions of states and governments. This collection provides expert analyses of such victimizations across the world, from Europe, the United States, and Africa to New Zealand and South America.
Contents note continued: 10.European Court of Human Rights: accountability to whom? / Isabel Schoultz -- 11.The victims of the Colombian conflict and restorative justice / Isabella Bueno -- 12.Institutional and structural victimisation: apartheid South Africa / Robert Peacock -- 13.Controlling state crime and the possibility of creating more victims / Peter Grabosky -- 14.Can an international criminal justice system address victims' needs? / Dawn L. Rothe.
Includes bibliographical references and index.
Keywords: State crimes; Victims of crimes; Human rights; Political atrocities